Highly conductive and stretchable carbon nanotube/thermoplastic polyurethane composite for wearable heater. (8th September 2019) - Sun, Wen-Jin; Xu, Ling; Jia, Li-Chuan; Zhou, Chang-Ge; Xiang, Yang; Yin, Ru-Hua; Yan, Ding-Xiang; Tang, Jian-Hua; Li, Zhong-Ming
Abstract: A stretchable, low-voltage, and deformation-stable heater was fabricated via a simple, efficient, and scalable process. Such heater integrates thermoplastic polyurethane (TPU) with segregated carbon nanotube (CNT) networks, exhibiting a high electrical conductivity of 142.6 S m −1 and the steady-state maximum temperature ( T MAX ) of 65 °C at only 6 V. The CNT/TPU heater maintains excellent temperature reliability during the heating-cooling stepwise cyclic operation. The attached tests to hand and wrist further prove the effective heat transfer and the compatibility of the CNT/TPU heater with the human skin. Moreover, 86% T MAX retention is achieved even when the heater undergoing 20% tensile strain and the T MAX could return to the original value once the strain released. The availability and reliability of our CNT/TPU heater under complex conditions demonstrate potential applications in next-generation wearable devices for human heating systems.